Aporte a las memorias desde las experiencias de dos documentales subjetivos santafesinos - Lidia G. Acuña (Nuevo mundo - Mundos Nuevos, 2012)
The Argentinian documentary film shows in its production the irruption of the director through the body, voice or a delegate actor, the presence of subjectivity that started to be observed in many pieces all over the country and also from different origins. These documentaries construct memories from new representations that enrich the autobiographical genre. These characteristics or different variations, in which the author subjectivity can be seen, will be approached through the analysis of two productions from Santa Fe: Un tal Ragone (deconstruyendo a pa), (Vanesa Ragone, 2002) y Madres con ruedas (Mario Piazza y Mónica Chirife, 2006). Thus, in our article, from the point of view of Cultural Studies, we find harmony and counterpoints between these productions, which show different ways of questioning and construing stories. These provide individual memories that become collective through the documentaries. These approaches have resulted in a broad utilization of different representation strategies for a task that in essence proves to be similar: recovery and reformulation of identity and history shifted from the public or private debate.